Energizing local communities—What motivates Irish citizens to invest in distributed renewables?. (February 2019) - Curtin, Joseph; McInerney, Celine; Gallachóir, Brian Ó.; Salm, Sarah
Highlights: There is high interest in distributed renewables in a market (Ireland) with no citizen investment tradition. Wealthy citizens with some investment experience are most interested. Financial investment attributes are of high importance, as is the technology. Developer-led renewable energy projects can provide opportunities to mobilise citizen investment. Major policy reform and incentives needed to promote citizen-led small and medium-sized projects. Abstract: Citizen investment in distributed renewables is becoming a key feature of low carbon transition in some countries, opening up new sources of capital and offering benefits for social support. Little is known about citizen investor preferences outside of mature markets such as Denmark and Germany, or if the experiences in these countries can be replicated elsewhere. Based on a survey of 1280 Irish citizens, 1000 of whom participated in a choice experiment, we find a high level of interest in investing in these technologies. This is particularly the case among high-income households with some investment experience. Investment amounts, however, are low compared to equity required for large projects, suggesting that citizen investors will not be a significant source of finance in these cases. Key barriers include lack of savings and no access to loan finance. A majority of citizens are highly risk-averse, and are motivated by financial attributes such as return and minimum investment holding period. Our findings suggest that developer-led projects may provide more opportunities for citizen investment, especially for large projects, and that significant policy interventions would be required targeting early-stage project risks to mobilise citizen investment in fully community-owned schemes.